Intramolecular energies of the cytotoxic protein CagA of Helicobacter pylori as a possible descriptor of strains' pathogenicity level. (October 2018) - Rojas-Rengifo, Diana F.; Alvarez-Silva, Maria Camila; Ulloa-Guerrero, Cindy P.; Nuñez-Velez, Vanessa Lucía; del Pilar Delgado, Maria; Aguilera, Sonia Milena; Castro, Harold; Jaramillo, Carlos Alberto; Fernando González Barrios, Andrés
Graphical abstract: Highlights: We found a relation between the H. pylori strain pathogenicity level, and the affinity of the interaction with SHP-2 and Grb2 receptors. Several energies allowed a separation between severe and mild pathology for the interaction of only CagA with SHP2. The energies that accounted for interactions were electrostatic, helix dipole, Wander Waals clashes, cis bond and torsional and backbone clash. Abstract: The Helicobacter pylori cytotoxin-associated gene A (CagA) is known for causing gastroduodenal diseases, such as atrophic gastritis and peptic ulcerations. Furthermore Helicobacter pylori CagA positive strains has been reported as one of the main risk factors for gastric cancer (Parsonnet et al., 1997). Structural variations in the CagA structure can alter its affinity with the host proteins, inducing differences in the pathogenicity of H. pylori. CagA N-terminal region is characterized for be conserved among all H. pylori strains since the C-terminal region is characterized by an intrinsically disorder behavior. We generated complete structural models of CagA using different conformations of the C-terminal region for two H. pylori strains. These models contain the same EPIYA (ABC1 C2 ) motifs but different level of pathogenicity: gastric cancer and duodenal ulcer. Using these structural models we evaluated the pathogenicity level of the H. pylori strain, based on the affinity of the interaction with SHP-2 and Grb2 receptors and on the number of interactions with the EPIYA motif. We found that the main differences in the interaction was due to the contributions of certain types of energies from each strain and not from the total energy of the molecule. Specifically, the electrostatic energy, helix dipole energy, Wander Waals clashes, torsional clash, backbone clash and cis bond energy allowed a separation between severe and mild pathology for the interaction of only CagA with SHP2.